Pengaruh Keputusan Investasi, Ukuran Perusahaan Dan Leverage Terhadap Nilai Perusahaan Pada Sektor Infrastruktur Yang Terdaftar Di Bei Periode 2019 -2023 - Nuraini Rahmatia Zahwa; Agnemas Yusoep Islami (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
This study aims to analyze the influence of investment decisions, firm size, and leverage on firm value in the infrastructure sector listed on the Indonesia Stock Exchange (IDX) for the period 2019-2023. This research employs quantitative methods using descriptive statistics and multiple linear regression analysis. The results show that simultaneously, the variables of investment decisions, firm size, and leverage significantly influence firm value, with a coefficient of determination of 98.3%. Partially, investment decisions and leverage have a significant negative effect on firm value, while firm size has a significant positive effect on firm value. This study provides important contributions to companies and investors in understanding the factors that affect firm value in the infrastructure sector.